(untitled) - Celko, Joe (California, 1999)
Data and Databases: Concepts in Practice is the first introduction to relational database technology written especially for practicing IT professionals. If you work mostly outside the database world, this book will ground you in the concepts and overall framework you must master if your data-intensive projects are to be successful. If you're already an experienced database programmer, administrator, analyst, or user, it will let you take a step back from your work and examine the founding principles on which you rely every day-helping you to work smarter, faster, and problem-free
Keywords: Data structures (computer science),Database management,Cấu trúc dữ liệu (khoa học máy tính),Quản trị cơ sở dữ liệu